2017
DOI: 10.1007/s00167-017-4585-8
|View full text |Cite
|
Sign up to set email alerts
|

No benefit of autologous transfusion drains in total knee arthroplasty

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Intraoperative red cell salvage is beneficial when there is 1L of blood loss; its efficiency is potentiated when combined with TXA as per the NICE guidelines (Thakrar et al 2017). However, Schnurr et al (2018) concluded that there is no beneficial effect in the utilisation of autologous transfusion drains. Additionally, a case control prospective study (Yin et al 2017) concluded that the use of a closed-suction drain in total knee arthroplasty does not confer any significant advantage, and that its use is redundant.…”
Section: Intraoperative Techniques Aimed At Reducing Blood Lossmentioning
confidence: 99%
“…Intraoperative red cell salvage is beneficial when there is 1L of blood loss; its efficiency is potentiated when combined with TXA as per the NICE guidelines (Thakrar et al 2017). However, Schnurr et al (2018) concluded that there is no beneficial effect in the utilisation of autologous transfusion drains. Additionally, a case control prospective study (Yin et al 2017) concluded that the use of a closed-suction drain in total knee arthroplasty does not confer any significant advantage, and that its use is redundant.…”
Section: Intraoperative Techniques Aimed At Reducing Blood Lossmentioning
confidence: 99%